Nano-Mole Scale Side-Chain Signal Assignment by 1H-Detected Protein Solid-State NMR by Ultra-Fast Magic-Angle Spinning and Stereo-Array Isotope Labeling - Wang, Songlin; Parthasarathy, Sudhakar; Nishiyama, Yusuke; Endo, Yuki; Nemoto, Takahiro; Yamauchi, Kazuo; Asakura, Tetsuo; Takeda, Mitsuhiro; Terauchi, Tsutomu; Kainosho, Masatsune; Ishii, Yoshitaka (PLoS ONE, 2015)
We present a general approach in 1H-detected 13C solid-state NMR (SSNMR) for side-chain signal assignments of 10-50 nmol quantities of proteins using a combination of a high magnetic field, ultra-fast magic-angle spinning (MAS) at ~80 kHz, and stereo-array-isotope-labeled (SAIL) proteins [Kainosho M. et al., Nature 440, 52–57, 2006]. First, we demonstrate that 1H indirect detection improves the sensitivity and resolution of 13C SSNMR of SAIL proteins for side-chain assignments in the ultra-fast MAS condition. 1H-detected SSNMR was performed for micro-crystalline ubiquitin (~55 nmol or ~0.5mg) that was SAIL-labeled at seven isoleucine (Ile) residues. Sensitivity was dramatically improved by 1H-detected 2D 1H/13C SSNMR by factors of 5.4-9.7 and 2.1-5.0, respectively, over 13C-detected 2D 1H/13C SSNMR and 1D 13C CPMAS, demonstrating that 2D 1H-detected SSNMR offers not only additional resolution but also sensitivity advantage over 1D 13C detection for the first time. High 1H resolution for the SAIL-labeled side-chain residues offered reasonable resolution even in the 2D data. A 1H-detected 3D 13C/13C/1H experiment on SAIL-ubiquitin provided nearly complete 1H and 13C assignments for seven Ile residues only within ~2.5 h. The results demonstrate the feasibility of side-chain signal assignment in this approach for as little as 10 nmol of a protein sample within ~3 days. The approach is likely applicable to a variety of proteins of biological interest without any requirements of highly efficient protein expression systems.
Keywords: Research Subject Categories::NATURAL SCIENCES::Chemistry; nano-mole; magic-angle spinning; MAS; stereo-array-isotope-labeled; SAIL; protein expression system